Climate Change and the Epidemiology of Infectious Diseases in the United States. (1st September 2022) - Edelson, Paul J; Harold, Rachel; Ackelsberg, Joel; Duchin, Jeffrey S; Lawrence, Steven J; Manabe, Yukari C; Zahn, Matt; LaRocque, Regina C
Abstract: The earth is rapidly warming, driven by increasing atmospheric carbon dioxide and other gases that result primarily from fossil fuel combustion. In addition to causing arctic ice melting and extreme weather events, climatologic factors are linked strongly to the transmission of many infectious diseases. Changes in the prevalence of infectious diseases not only reflect the impacts of temperature, humidity, and other weather-related phenomena on pathogens, vectors, and animal hosts but are also part of a complex of social and environmental factors that will be affected by climate change, including land use, migration, and vector control. Vector- and waterborne diseases and coccidioidomycosis are all likely to be affected by a warming planet; there is also potential for climate-driven impacts on emerging infectious diseases and antimicrobial resistance. Additional resources for surveillance and public health activities are urgently needed, as well as systematic education of clinicians on the health impacts of climate change. Abstract : Climate change is the major global public health challenge of our time. The Earth's climate has already been seriously changed, and the epidemiology of infectious diseases will be affected. Infectious disease clinicians and public health practitioners must be prepared to address these changes.